2019
DOI: 10.31018/jans.v11i2.2039
|View full text |Cite
|
Sign up to set email alerts
|

Polygalacturonase production by Aspergillus nomius MR103 in solid state fermentation using Agro-industrial wastes

Abstract: The present study was aimed at polygalacturonase production from Aspergillus nomius MR103 under solid state fermentation. A total of 57 fungal strains were obtained from mangrove soils collected from Gilakaladindi and Malakayalanka of Krishna District Andhra Pradesh. For the isolation of fungi these Soil samples were serially diluted and plated on pectin agar media plates.  Among them, the isolate which showed maximum polygalacturonase activity was selected for this study. This strain was identified as A. nomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
4
3
0
Order By: Relevance
“…Moreover, the generation of growth biomass showed a similar kind of trend with respect to pH which was maximum (0.114 ± 0.003 g/50 ml) at pH 7.0 (Figure 2a). The results are in concordance with the findings of Barkavi et al [45] and Ketipally et al [46] who have used A. niger and A. nomius, respectively. Various microbes are also known to produce pectinase that is active at higher pH and is termed alkaline pectinase.…”
Section: Effect Of Initial Ph (Medium) On the Pectinase Productionsupporting
confidence: 93%
See 3 more Smart Citations
“…Moreover, the generation of growth biomass showed a similar kind of trend with respect to pH which was maximum (0.114 ± 0.003 g/50 ml) at pH 7.0 (Figure 2a). The results are in concordance with the findings of Barkavi et al [45] and Ketipally et al [46] who have used A. niger and A. nomius, respectively. Various microbes are also known to produce pectinase that is active at higher pH and is termed alkaline pectinase.…”
Section: Effect Of Initial Ph (Medium) On the Pectinase Productionsupporting
confidence: 93%
“…In the present investigation, the organism was cultured with AP, where the culture has to produce the enzyme required for degrading the substrate, followed by utilization of the same for growth that explains the slow growth and production of pectinase which strongly support with findings of Barkavi et al [45], Abbasi et al [34] and Ketipally et al [46]. A few strains of Aspergillus are also known to produce pectinase in a short period of time [41,46,48]. The time required for fermentation depends upon certain factors such as the amount of nutrients in the medium, nature of the medium, physiological parameters and fermentative microorganisms [49,50].…”
Section: Effect Of Incubation Time On the Pectinase Productionsupporting
confidence: 86%
See 2 more Smart Citations
“…Sucrose improved exo-polygalacturonase production in ssf system while a marked inhibition was observed in smf (Fig. 2), supported by Ketipally et al [18] who observed that addition of sucrose to orange peel media improved the polygalacturonase production in solid-state fermentation of Aspergillus nomius. Enzyme induction ratio of tannase [19] and xylanase [20] in the presence of sucrose was also reported to increase in solid-state fermentation.…”
Section: Discussionsupporting
confidence: 69%